THE POLITICS OF FOOD DISTRIBUTION DURING THE COVID-19 LOCK DOWN IN UGANDA. - Nabukeera, Madinah (Archives of Business Research, 2020)
In face of the Novel Covid-19 pandemic that has swept the world, Ugandan President Yoweri Museveni issued clear rules; stay at home unless it’s an emergency, wash your hands, sanitize, report any related cases for contact tracing and testing. In his directive all passenger services were stopped including private vehicles and imposed a curfew 7 pm until 6:30 a.m., which made stay at home orders mandatory. Majority of Ugandan urban dwellers are hand-to -mouth and live off their capability to move to town centers daily a small interruption in their routine means many went hungry. The government of Uganda broadcasted measures to distribute relief food items to troubled and vulnerable population mainly in the towns since those in the country sides are able to grow food and provide for their families. This article articulates the politics in the food in Wakiso and Kampala districts in Uganda why there was bias. The study used the selected all documents related to food distribution using content analysis and results indicated that anyone found distributing food outside the national covid-19 task force will be charged with attempted murder hence stopped politicians from strategizing ahead of 2021 parliamentary, presidential and local elections which implied that Covid-19 disrupted over 134 districts in the country in line with the preparation of elections and left majority hungry.